Polystyrene and poly(methyl methacrylate) interfaces reinforced with diblock carbon nanotubes. Issue 4 (11th February 2021) - Seyni, Fatoumata Ide; Barrett, Lawrence; Crossley, Steven; Grady, Brian P.
Abstract: An asymmetric double cantilever beam test was used to determine the ability of carbon nanotubes with varying chemistry along their lengths, that is, diblock nanotubes, to compatibilize the polystyrene/poly(methyl methacrylate) (PS/PMMA) interface. PS molecules were grafted primarily to one of the blocks to cause that block to migrate to the PS phase since otherwise both blocks would prefer to reside in PMMA. Fracture toughnesses increased monotonically with increasing diblock carbon nanotube concentration and maximum values were like those for block copolymer‐reinforced interfaces while single‐chemistry nanotubes showed no reinforcing effect. However, the abrupt increase in fracture toughness with added compatibilizer indicative of a transition to crazing was not found consistent with nanotubes suppressing crazing in homopolymers. Scanning electron microscopy images of the fractured surfaces show agglomerates of carbon nanotubes present which are likely limiting the efficacy of carbon nanotubes at toughening the interface. Abstract :